Late effects on the health-related quality of life in a cohort population decades after environmental radiation exposure - Yen, Pimei Nancy; Yang, Chen-Chang; Chang, Wushou Peter; Wang, Jung-Der; Hwang, Jing-Shiang; Chang, Tien-Chun; Kuo, Kuan-Liang; Lin, I-Feng (International journal of radiation biology, 2013)
Abstract Purpose: To evaluate the late effects on the quality of life (QOL) of individual years after protracting low-dose radiation exposure. Materials and methods: We assessed 1,818 subjects using the World Health Organization Questionnaire on Quality of Life - Brief Version (WHOQOL-BREF) in several Health-Related Quality of Life (HRQoL) domains. After adjusting for demographic characteristics and comorbidities, we examined the HRQoL differences at various levels of exposure and ages at disclosure. We also evaluated the potential effect modification by gender. Results: After adjusting for potential confounders, girls aged 12 years or younger at the disclosure of exposure had lower HRQoL scores in physical, psychological, and environmental domains compared to those with later age at disclosure. The differences in the HRQoL scores between different exposure subgroups were not significant in physical, psychological, and social relationship domains, and only appeared in the environmental domain. Conclusions: Being female and less than 12 years of age at disclosure were more significant predictors of HRQoL scores than the levels of radiation exposure among people exposed to protracted low-dose radiation. Further studies are needed to determine the psychological distresses, such as depression and anxiety, and their relationships in this case, especially for the most vulnerable young females.